1999
DOI: 10.1111/j.1469-7793.1999.0803p.x
|View full text |Cite
|
Sign up to set email alerts
|

Actions of opioids on excitatory and inhibitory transmission in substantia gelatinosa of adult rat spinal cord

Abstract: The actions of opioid receptor agonists on synaptic transmission in substantia gelatinosa (SG) neurones in adult (6‐ to 10‐week‐old) rat spinal cord slices were examined by use of the blind whole‐cell patch‐clamp technique. Both the μ‐receptor agonist DAMGO (1 μM) and the δ‐receptor agonist DPDPE (1 μM) reduced the amplitude of glutamatergic excitatory postsynaptic currents (EPSCs) which were monosynaptically evoked by stimulating Aδ afferent fibres. Both also decreased the frequency of miniature EPSCs without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
185
1
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(210 citation statements)
references
References 44 publications
23
185
1
1
Order By: Relevance
“…It has been shown that the release of glutamate and substance P from primary afferent neurons is inhibited by δ-opioid agonists (Glaum et al, 1994;Kohno et al, 1999;Kondo et al, 2005). Thus, the presynaptic action of δ-opioid agonists on nociceptive afferent terminals has been considered an important mechanism underlying the spinal analgesic effect of δ-opioid agonists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the release of glutamate and substance P from primary afferent neurons is inhibited by δ-opioid agonists (Glaum et al, 1994;Kohno et al, 1999;Kondo et al, 2005). Thus, the presynaptic action of δ-opioid agonists on nociceptive afferent terminals has been considered an important mechanism underlying the spinal analgesic effect of δ-opioid agonists.…”
Section: Discussionmentioning
confidence: 99%
“…Spinally administered δ-opioid agonists likely inhibit synaptic transmission through both pre-and postsynaptic mechanisms (Abbadie et al, 2002;Glaum et al, 1994;Kohno et al, 1999;Stewart and Hammond, 1993;Zachariou and Goldstein, 1996). The opioid receptors are coupled to inhibitory G proteins, and voltage-activated Ca 2+ channels are an important downstream signaling target for the opioid analgesic action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although cannabinoids and opioids both produce analgesia within the dorsal horn, their pharmacologic mechanisms of action differ. For instance, -opioid receptor agonists inhibit release of glutamate from primary afferent terminals at the level of the spinal and medullary dorsal horn, while CB 1 receptors do not have any inhibitory effect on those excitatory neurons [49,81]. Moreover, -opioid receptors presynaptically inhibit both glycinergic and GABAergic synaptic transmission in the medullary dorsal horn [48], but not in the spinal cord [81], as occurs with CB 1 receptors.…”
Section: Cannabinoids and Opioids Analgesic Synergismmentioning
confidence: 99%
“…For instance, -opioid receptor agonists inhibit release of glutamate from primary afferent terminals at the level of the spinal and medullary dorsal horn, while CB 1 receptors do not have any inhibitory effect on those excitatory neurons [49,81]. Moreover, -opioid receptors presynaptically inhibit both glycinergic and GABAergic synaptic transmission in the medullary dorsal horn [48], but not in the spinal cord [81], as occurs with CB 1 receptors. There are other differences at the supraspinal level, where both cannabinoid and opioid recep-tors presynaptically inhibit GABAergic synaptic transmission, disinhibiting nociceptive descending projection neurons, but only -opioid receptors directly inhibit putative GABAergic neurons in the PAG and RVM [19,162,163].…”
Section: Cannabinoids and Opioids Analgesic Synergismmentioning
confidence: 99%